A case report on tricyclic antidepressant induced increased blood pressure - Jacson, Janice (Indian Journal of Pharmacy & Drug Studies, 2023)
This is a case of antidepressant-masked high blood pressure. Administration of tricyclic antidepressants that cause raised blood pressure becomes particularly important in resistant hypertension cases. In this case, we report a case of raised blood pressure despite multiple antihypertensives. The patient also presented with electrolyte imbalances also raising the suspicion of drug side effects due to unnecessary drugs administered. Therefore, arriving at a clinical decision with minimal side effects and focused treatments requires identifying every detail of the patient, including their medical and medication histories.